Pengaruh Job Insecurity dan Pengawasan Kerja terhadap Kedisiplinan Kerja Karyawan Outsourcing pada PT Airkon Pratama Project RSUD Kota Bekasi - Cucu Solihah; Hendra Kurniawan (PT Cakrawarti Empat Proksi, 2026)
Work discipline is one of the essential factors in supporting organizational effectiveness, particularly for outsourced employees who are required to perform their duties in accordance with established operational standards. However, several conditions, including job insecurity and inadequate work supervision, may influence employees' level of discipline. This study aims to analyze the effect of job insecurity and work supervision on the work discipline of outsourced housekeeping employees at PT Airkon Pratama, RSUD Kota Bekasi Project. This research employed a quantitative descriptive approach. The population consisted of 100 outsourced housekeeping employees, while the sample comprised 74 respondents selected using purposive sampling techniques. Data were collected through questionnaires and analyzed using Statistical Package for the Social Sciences (SPSS), including validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, partial hypothesis testing (t-test), simultaneous hypothesis testing (F-test), and coefficient of determination analysis. The findings indicate that job insecurity and work supervision significantly influence employees' work discipline. Simultaneously, both independent variables contribute significantly to improving work discipline. Therefore, strengthening supervisory practices and managing employees' perceptions of job insecurity are essential strategies for improving organizational discipline. The findings are expected to provide valuable insights for organizations in developing more effective human resource management policies.